Β-Structure within the Denatured State of the Helical Protein Domain BBL. Issue 19 (25th September 2015) - Thukral, Lipi; Schwarze, Simone; Daidone, Isabella; Neuweiler, Hannes
Abstract: Protein denatured states are the origin of both healthy and toxic conformational species. Denatured states of ultrafast folding proteins are of interest in mechanistic studies because they are energetically close to the kinetic bottleneck of folding. However, their transient nature makes them elusive to experiment. Here, we generated the denatured state of the helical domain BBL that is poised to fold in microseconds by a single-point mutation and combined circular dichroism spectroscopy, single-molecule fluorescence fluctuation analysis, and computer simulation to characterize its structure and dynamics. Circular dichroism showed a largely unfolded ensemble with marginal helix but significant β-sheet content. Main-chain structure and dynamics were unaffected by side-chain interactions that stabilize the native state, as revealed by site-directed mutagenesis and nanosecond loop closure kinetics probed by fluorescence correlation spectroscopy. Replica-exchange and constant-temperature molecular dynamics simulations showed a highly collapsed, hydrogen-bonded denatured state containing turn and β-sheet structure and few nucleating helices in an otherwise unfolded ensemble. An irregular β-hairpin element that connects helices in the native fold was poised to be formed. The surprising observation of β-structure in regions that form helices in the native state is reconciled by a generic low-energy pathway from the northwest quadrant of Ramachandran space to the helical basin present under folding conditions, proposed recently. Our results show that, indeed, rapid nucleation of helix emanates from β-structure formed early within a collapsed ensemble of unfolded conformers. Graphical abstract: Highlights: Protein denatured states are elusive to experimental characterization. We combined experiment with computer simulation to achieve this goal. We find β-structure within the denatured state of a helical domain. Early formation of β/turn structure appears to precede nucleation of helix.